Frequent respiratory events in postoperative patients aged 60 years and above - Broens SJL; He X; Evley R; Olofsen E; Niesters M; Mahajan RP; Dahan A; van Velzen M (Dove Medical Press, 2017)
Suzanne JL Broens,1 Xuan He,1 Rachel Evley,2 Erik Olofsen,1 Marieke Niesters,1 Ravi P Mahajan,2 Albert Dahan,1 Monique van Velzen1 1Department of Anesthesiology, Leiden University Medical Centre, Leiden, the Netherlands; 2Nottingham University Hospital NHS Trust, Queen’s Medical Centre, Nottingham, UK Abstract: There is limited information on the occurrence of respiratory events in postoperative patients after discharge from the postanesthesia care unit. We studied the respiratory rate (RR) of 68 patients aged 60 years and above during the first 6 hours following elective surgery under general anesthesia to assess the frequency of respiratory events in the care unit and on the ward. RR was derived from the continuous RR counter RespiR8, measuring RR by quantifying the humidity of exhaled air. One-minute-averaged RRs were collected and analyzed to assess the frequency of postoperative bradypnea (RR 1–6 breaths/minute) and apnea (cessation of inspiratory flow ≥60 seconds). Values were median (interquartile range) or mean (SD). The median RR was 13 (10–15) breaths/minute. In the 6-hour postoperative period, 78% and 57% of patients experienced at least one bradypnea or apnea event, respectively. A median of ten (3.5–24) bradypnea and three (1–11) apnea events were detected per patient. The occurrence of respiratory events in the postanesthesia care unit (PACU) was a predictor of events on the ward (bradypnea, r2=0.4, P<0.001; apnea, r2=0.2, P<0.001). Morphine consumption correlated weakly with respiratory events in the PACU, but not on the ward. Patients with apnea had significantly larger neck circumference than patients without (39.6 [0.7] versus 37.4 [0.8] cm, P<0.05). Bradypneic or apneic respiratory events are frequent in postoperative elderly patients and even occur relatively late after surgery. Continuous respiratory monitoring on the ward, especially in patients with risk factors, such as early occurrence of events, opioid use, and larger neck circumference, is likely warranted. Keywords: aged, monitoring, physiologic, postoperative period, respiratory insufficiency, respiratory rate